THE EFFECT OF COMPANY SIZE, DEBT POLICY, AND PROFITABILITY ON COMPANY - Masta Sembiring; Trie Meutia Defi (RADJA PUBLIKA, 2022)
The purpose of this study is to test and analyze the effect of Company Size on Firm Value, to test and analyze Debt Policy on Firm Value, to test and analyze Profitability on Firm Value and to test and analyze the effect of Company Size, Debt Policy and Profitability on Firm Value. in Real Estate Companies listed on the IDX. The population used in this study were Real Estate and Property companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019 and samples from research on Real Estate and Property companies were 10 companies with 5 years of observation. The data collection technique used in this research is documentation. The analysis technique used in this research is descriptive statistics, multiple linear regression analysis, partial test, determinant test. The results showed that partially firm size has a significant effect on firm value, partially debt policy has no significant effect on firm value, partially profitability affects firm value and simultaneously shows that firm size, debt policy and profitability have a significant effect on firm value In Real Estate Companies Listed on the IDX.